Study of Blood-transfusion Services in Maharashtra and Gujarat States, India (Journal of Health, Population and Nutrition, 2009)
Blood-transfusion services are vital to maternal health because haemorrhage and anaemia are major causes of maternal death in South Asia. Unfortunately, due to continued governmental negligence, blood-transfusion services in India are a highly-fragmented mix of competing independent and hospital-based blood-banks, serving the needs of urban populations. This paper aims to understand the existing systems of blood-transfusion services in India focusing on Maharashtra and Gujarat states. A mix of methodologies, including literature review (including government documents), analysis of management information system data, and interviews with key officials was used. Results of analysis showed that there are many managerial challenges in blood-transfusion services, which calls for strengthening the planning and monitoring of these services. Maharashtra provides a good model for improvement. Unless this is done, access to blood in rural areas may remain poor. Key words: Blood-banks; Blood-storage centres; Blood transfusion; Emergency obstetric care; India doi: 10.3329/jhpn.v27i2.3368 J Health Popul Nutr 2009 April;27(2):259-270